Chlorpyrifos induces redox imbalance‐dependent inflammation in common carp lymphocyte through dysfunction of T‐cell receptor γ. Issue 4 (11th February 2020) - Yang, Jie; Gong, Yafan; Cai, Jingzeng; Zheng, Yingying; Liu, Honggui; Zhang, Ziwei
Abstract: Chlorpyrifos is a poisonous pesticide that is highly toxic to fish and aquatic organisms. However, there are fewer reports about how chlorpyrifos influences the redox balance of immune cells. Herein, the head kidney tissue treated with chlorpyrifos to do transcriptome analysis and TCR γ was screened out. Subsequently, we established TCR γ knockdown and overexpression carp head kidney lymphocyte models, respectively, by using RNA interference and pcDNA3.1. Real‐time PCR, fluorescent staining, oxidation and antioxidant kit were used to detect the related factors. We found that TCR γ knockdown significantly increased the mRNA expression of HSP70 and HSP90 and decreased the mRNA expression of SOD and CAT. Meanwhile, TCR γ knockdown reduced the activities of GSH, GSG‐PX, T‐AOC, CAT and SOD and increased the content of MDA and H2 O2 and activities of iNOS. Adverse results were obtained in TCR γ overexpression group. Additionally, TCR γ knockdown significantly increased the mRNA expression of IFN‐γ, IL‐1β, IL‐8, IL‐10, Nrf2 and NF‐κB, but relieved TCR γ overexpression, in which the process of inflammation was activated. Our results reported here indicated that chlorpyrifos induces redox imbalance‐dependent inflammation in common carp lymphocyte through dysfunction of T‐cell receptor γ, and HSPs play potential protective role in entire process.